Investigations of amphiphilic butylglyceryl-functionalized dextran nanoparticles for topical delivery - F. Bostanudin, Mohammad; Muhamad Noor, Noor S.; Sahudin, Shariza; Mat Lazim, Azwan; Suk, Fei Tan; Sarker, Md. Zaidul Islam (Wiley-Blackwell, 2020)
Toward the development of colloidal systems that can enhance transdermal permeation of hydrophilic actives, a material combining the non‐toxic of dextran with alkylglycerols permeation enhancing property has been designed. To this purpose, a range of amphiphilic butylglyceryl dextrans (DEX‐OX4) was synthesized via modification with n‐butylglycidyl ether with a degree of functionalization in the range 6.3%–35.7%. A reduced viscosity and an increased molecular weight of DEX‐OX4 were recorded when compared to the starting material. DEX‐OX4 was formulated into nanocarriers and loaded with α‐arbutin prior to characterization—the nanoparticles (180–220 nm size) were found to be close‐to‐spherical, stable at pH 5 and 7, with a loading capacity of 11.7%. Slower release of α‐arbutin from the nanoparticles was demonstrated when tested in acidic media. Lack of toxicity at application‐relevant concentrations and increased permeation were demonstrated by nanoparticles in vitro results against immortalized skin human keratinocytes cells (HaCaT).